Clinicans' views and experiences of two alternative consent pathways for participation in a preterm intrapartum trial: a qualitative study - Chhoa, Celine Y.; Sawyer, Alexandra; Ayers, Susan; Pushpa-Rajah, Angela; Duley, Lelia (BioMed Central, 2017)
Background